Strategi Konten Interaktif dan Persepsi Nilai serta Keterlibatan Konsumen di PT. Indo Bismar Surabaya - Nabila Faiqoh; Hanafi Adi Putranto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze interactive content strategies, value perceptions, and consumer engagement at PT. Indo Bismar Surabaya. The background of this study is based on the increasingly dominant trend of short video-based marketing on social media, yet Indo Bismar's consumer engagement levels remain limited. The research method uses a qualitative approach with a case study design. Data was collected through semi-structured interviews with digital marketing staff, interns, and consumers, and reinforced by observing content on the company's official Instagram account. The analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that Indo Bismar's content strategy is dominated by entertainment content oriented towards visibility, while product information only receives a small portion. The creativity of the internship team strengthens content implementation, but limited human resources and budget hinder consistency. Consumers rate content value higher when information, entertainment, and interactivity are present simultaneously, which ultimately increases engagement. This study confirms that the success of digital marketing depends not only on content creativity, but also on the organization's ability to strategically manage internal resources.